Inconsistencies and misleading information in officially approved prescribing information from three major drug markets - Pfistermeister, Barbara; Saß, Anke; Criegee-Rieck, Manfred; Bürkle, Thomas; Fromm, Martin; Maas, Renke (Clinical Pharmacology & Therapeutics, 2014)
The summary of product characteristics (SPC) should provide information for the safe prescription and use of a drug. We evaluated the consistency of critical interaction warnings, the quality of presentation of undesirable effects as well as concordance of critical information of representative drugs marketed in the United States, the UK, and Germany. Reciprocal warnings regarding drug-drug interactions that constitute contraindications were frequently missing in the SPCs of the drugs concerned (all countries >40%). Most SPCs did not explicitly exclude adverse reactions considered not reasonably attributable to the use of the drug. Comparing SPCs of different generic brands of the same drug, only 60, 10, and 20% of the US, UK, and German SPCs, respectively, provided identical contraindications. Current SPCs contain inconsistencies and misleading data that are not compatible with the purpose of SPCs, which is to provide a basis for the safe prescription and use of drugs.
EVALuna2:129

Memorandum on the use of information technology to improve medication safety - Ammenwerth, E.; Aly, A. -F.; Bürkle, Thomas; Christ, P.; Dormann, Harald; Friesdorf, W.; Haas, C.; Haefeli, W. E.; Jeske, M.; Kaltschmidt, J.; Menges, K.; Moeller, H.; et al. (Methods of Information in Medicine, 2014)
Information technology in health care has a clear potential to improve the quality and efficiency of health care, especially in the area of medication processes. On the other hand, existing studies show possible adverse effects on patient safety when IT for medication-related processes is developed, introduced or used inappropriately.To summarize definitions and observations on IT usage in pharmacotherapy and to derive recommendations and future research priorities for decision makers and domain experts.This memorandum was developed in a consensus-based iterative process that included workshops and e-mail discussions among 21 experts coordinated by the Drug Information Systems Working Group of the German Society for Medical Informatics, Biometry and Epidemiology (GMDS).The recommendations address, among other things, a stepwise and comprehensive strategy for IT usage in medication processes, the integration of contextual information for alert generation, the involvement of patients, the semantic integration of information resources, usability and adaptability of IT solutions, and the need for their continuous evaluation.Information technology can help to improve medication safety. However, challenges remain regarding access to information, quality of information, and measurable benefits.
EVALuna2:131

Tailored e-Health services for the dementia care setting: a pilot study of 'eHealthMonitor' - Schaller, Sandra; Marinova-Schmidt, Velislava; Gobin, Jasmin; Criegee-Rieck, Manfred; Griebel, Lena; Engel, Sabine; Stein, Veronika; Grässel, Elmar; Kolominsky-Rabas, Peter (BMC Medical Informatics and Decision Making, 2015)
The European eHealthMonitor project (eHM) developed a user-sensitive and interactive web portal for dementia care: the eHM Dementia Portal (eHM-DP). It aims to provide targeted and personalized support for informal caregivers of people with dementia in a home-based care setting. The objective of the pilot study was to obtain feedback on the eHM-DP from two user perspectives (caregivers and medical professionals), focusing on caregiver empowerment, decision aid, and the perceived benefits of the eHM-DP.The study on the eHM-DP was conducted from March 2014 to June 2014. The methodological approach followed a user-participatory design with a total number of 42 participants. The study included caregivers of people with dementia and medical professionals (MPs) from the metropolitan region of Erlangen-Nürnberg (Bavaria, Germany). Study participants were interviewed face-to-face with semi-structured, written interviews.Caregivers indicated a high degree of perceived support by the eHM-DP and of provided decision aid. In total, 89 % of caregivers and 54 % of MPs would use the eHM-DP if access were provided. The primary benefits participants perceived were the acquisition of individualized information, computerized interaction between caregivers and MPs, empowerment in health-related decisions and comprehensive insights into the progress of the disease. Major recommendations for improving the eHM-DP encompassed: an active search functionality based on predefined terms, the implementation of a chatroom for caregivers, an upload function and alerts for MPs, as well as the overall design.Our study is the first to have provided new insights and results on an interactive and needs-oriented web portal, endeavouring towards empowerment and assistance in decision making for caregivers as well as MPs within the realm of caring for patients with dementia. The acceptance and willingness to use the eHM-DP emphasizes the potential of eHealth services for community-based dementia care settings.
EVALuna2:152

Zum Einsatz von Informationstechnologie zur Verbesserung der Arzneimitteltherapiesicherheit (Memorandum AMTS-IT) - Aly, Amin Farid; Bürkle, Thomas; Christ, Petra; Dormann, Harald; Friesdorf, Wolfgang; Haas, Christine; Haefeli, Walter E.; Jeske, Martina; Kaltschmidt, Jens; Menges, Klaus; Möller, Horst; Neubert, Antje; et al. (Deutsche Gesellschaft fur Medizinische Informatik, Biometrie und Epidemiologie e.V. (GMDS), 2014)
Information technology in health care has a clear potential to improve quality and efficiency of health care, especially in the area of medication processes. On the other side, existing studies show possible adverse effects on patient safety when IT for medication-related processes is developed, introduced or used inappropriately. The objective of this paper is to summarize definitions and observations on IT usage in pharmacotherapy, and to derive recommendations and future research priorities for decision makers and domain experts. The recommendations address, among others, a stepwise and comprehensive strategy for IT usage in medication processes, the integration of contextual information for alert generation, the involvement of patients, the semantic integration of information resources, usability and adaptability of IT solutions and the need for their continuous evaluation.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Decision support systems; Drug therapy safety; Information technology; Medication safety; Medication safety; Patient safety